Pengaruh Model Pembelajaran Course Review Horay (CRH) Terhadap Hasil Belajar Siswa - Nureva Nureva; Siska Wulandari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This article aimed to analyze the influence of Course Review Horay (CRH) learning model on social study learning result at fifth grade of elementary school 5 of Merak Batin South Lampung. This research was a quantitative research with the type of Posttest-Only Control Designe. Techniques for analyzing data were analyzed using the t-test. The result show that the type hypothesis testing obtained Tcount results> Ttable is Tcount of 7,81 with Ttable 1,67 with a significant level of 0,05. Which means Ha accepted and H0 rejected. Thus there is an influence between the Course Review Horay (CRH) learning model on social studies learning outcome at the fifth grade elementary school 5 Merak Batin in the inner south lampung. Key words: Course Review Horay Learning Model, Learning Outcome, Social Study